Representation of Morality in the KKN Film in the Dance Village Director Awi Suryadi - Abun, Abun; Anwari, Anwari (Program Studi Komunikasi dan Penyiaran Islan STAIMAS Wonogiri, 2025)
Film is one of the mass communication media that is often used to reflect the social life of the community. As part of the mass media, film serves as an effective communication tool. For example, the film KKN in Penari Village tells the story of six people who are carrying out KKN in a village that is quite remote. The film highlights moral conflicts, behavioral patterns, values, social and cultural influences, and ethical conflicts. This research aims to answer two main questions: (1) How are the signs of morality depicted in the film